Nano-scale wear characterization of CoCrMo biomedical alloys. (January 2016) - Martinez-Nogues, V.; Nesbitt, J.M.; Wood, R.J.K.; Cook, R.B.
Abstract: Low amplitude motions at the micro and the nano-scale at the femoral stem–cement interface under physiological loads can result in fretting and nano-wear on the stem surface. These are important wear processes in cemented total hip replacements as the release of metal debris and ions can trigger adverse local tissue reactions within the body, bone resorption and subsequent aseptic loosening of the femoral component resulting in the implant failure. However, the influence of the microstructure and manufacturing processes on the nano-wear behaviour of different cobalt chromium molybdenum (CoCrMo) alloys has not been studied extensively. Four CoCrMo alloys were tested under reciprocating wear conditions at the nano-scale level. Tangential friction forces, coefficient of friction and plastic deformation values were recorded. A new white-light-interferometer system was validated against atomic force microscopy and Nano Vantage Test System measurements to analyse the permanent plastic deformation caused in each of the samples. Significant differences were found in the total plastic deformation achieved by the as cast alloy compared to the forged, as cast single thermal treated and as cast double thermal treated samples. In addition thermal treated samples presented a tendency to produce a higher quantity of wear debris around the nano-wear scars. These findings indicate a possible relation between the wear resistance at the nano-scale and the manufacturing and thermal processes applied on the CoCrMo biomedical alloys. Highlights: Forged CoCrMo exhibited higher nano-wear resistance than as cast CoCrMo alloys. Forged alloy showed the highest dispersed energy per cycle values. Thermal treatments increase the wear debris generation nearby the nano-wear scar. New white-light-interferometer system validated to measure plastic deformation at the nano-scale.